Extremely low-energy ARPES of quantum well states in cubic-GaN/AlN and GaAs/AlGaAs heterostructures - Hajlaoui, Mahdi; Ponzoni, Stefano; Deppe, Michael; Henksmeier, Tobias; As, Donat Josef; Reuter, Dirk; Zentgraf, Thomas; Springholz, Gunther; Schneider, Claus Michael; Cramm, Stefan; Cinchetti, Mirko (Scientific Reports)
Abstract Quantum well (QW) heterostructures have been extensively used for the realization of a wide range of optical and electronic devices. Exploiting their potential for further improvement and development requires a fundamental understanding of their electronic structure. So far, the most commonly used experimental techniques for this purpose have been all-optical spectroscopy methods that, however, are generally averaging in momentum space. Additional information can be gained by angle-resolved photoelectron spectroscopy (ARPES), which measures the electronic structure with momentum resolution. Here we report on the use of extremely low-energy ARPES (photon energy ~ 7 eV) to increase depth sensitivity and access buried QW states, located at 3 nm and 6 nm below the surface of cubic-GaN/AlN and GaAs/AlGaAs heterostructures, respectively. We find that the QW states in cubic-GaN/AlN can indeed be observed, but not their energy dispersion, because of the high surface roughness. The GaAs/AlGaAs QW states, on the other hand, are buried too deep to be detected by extremely low-energy ARPES. Since the sample surface is much flatter, the ARPES spectra of the GaAs/AlGaAs show distinct features in momentum space, which can be reconducted to the band structure of the topmost surface layer of the QW structure. Our results provide important information about the samples’ properties required to perform extremely low-energy ARPES experiments on electronic states buried in semiconductor heterostructures.

The ‚teachwodd training concept’ a contribution to the implementation of practical technological learning in primary schools. - Tenberge, Claudia; Gödiker, Manon

Load Data Acquisition in Rural East Africa for the Layout of Microgrids and Demand–Side–Management Measures - Kakande, Josephine Nakato; Philipo, Godiana Hagile; Krauter, Stefan (Proceedings of the 38th European Photovoltaic Solar Energy Conference and Exhibition (EUPVSEC 2021))
With its growing population and industrialization, DREs, and solar technologies in particular, provide a sustainable means of bridging the current energy deficit in Africa, increasing supply reliability and meeting future demand. Data acquisition and data management systems allow real time monitoring and control of energy systems as well as performance analysis. However commercial data acquisition systems often have cost implications that are prohibitive for small PV systems and installations in developing countries. In this paper, a multi-user, multi-purpose microgrid database system is designed and implemented. MAVOWATT 270 power quality analyzers by GOSSEN METRAWATT, raspberry pi modules and sensors are used for measuring, recording and storing electrical and meteorological data in East Africa. Socio-economic data is also stored in the database. The designed system employs open source software and hardware solutions which are best suited to developing regions like East Africa due to the lower cost implications. The expected results promise a comprehensive database covering different electro-technical and socio-economic parameters useful for optimal design of microgrid systems.
Keywords: Art-D; Afrika; Demand side management; MySQL; Raspberry pi; Data acquisition

Diagnosen (h)erstellen – Sprachwissenschaftliche Zugänge - Felder, Ekkehard; Schuster, Britt-Marie; Spranz-Fogasy, Thomas (Linguistik und Medizin)
Keywords: Fachkommunikation

Widersprechen als diskursive Praktik. Illustriert an der Widerstandskommunikation gegen den Nationalsozialismus (1933–1945) - Schuster, Britt-Marie (Protest, Protestieren, Protestkommunikation)
Keywords: Kommunikationsgeschichte

Bedeutungsvarianz und sozialer Stil - Schuster, Britt-Marie; Wilk, Nicole M. (Sprache des Sterbens – Sprache des Todes. Linguistische und interdisziplinäre Perspektivierungen eines zentralen Aspekts menschlichen Daseins)
Keywords: Textsemantik

Peeking beyond peaks: Challenges and research potentials of continuous multimodal multi-objective optimization - Grimme, Christian; Kerschke, Pascal; Aspar, Pelin; Trautmann, Heike; Preuss, Mike; Deutz, André H.; Wang, Hao; Emmerich, Michael (Computers & Operations Research)
Multi-objective (MO) optimization, i.e., the simultaneous optimization of multiple conflicting objectives, is gaining more and more attention in various research areas, such as evolutionary computation, machine learning (e.g., (hyper-)parameter optimization), or logistics (e.g., vehicle routing). Many works in this domain mention the structural problem property of multimodality as a challenge from two classical perspectives: (1) finding all globally optimal solution sets, and (2) avoiding to get trapped in local optima. Interestingly, these streams seem to transfer many traditional concepts of single-objective (SO) optimization into claims, assumptions, or even terminology regarding the MO domain, but mostly neglect the understanding of the structural properties as well as the algorithmic search behavior on a problem’s landscape. However, some recent works counteract this trend, by investigating the fundamentals and characteristics of MO problems using new visualization techniques and gaining surprising insights. Using these visual insights, this work proposes a step towards a unified terminology to capture multimodality and locality in a broader way than it is usually done. This enables us to investigate current research activities in multimodal continuous MO optimization and to highlight new implications and promising research directions for the design of benchmark suites, the discovery of MO landscape features, the development of new MO (or even SO) optimization algorithms, and performance indicators. For all these topics, we provide a review of ideas and methods but also an outlook on future challenges, research potential and perspectives that result from recent developments.
Keywords: Multimodal optimization; Multi-objective continuous optimization; Landscape analysis; Visualization; Benchmarking; Theory; Algorithms

On the Potential of Normalized TSP Features for Automated Algorithm Selection - Heins, Jonathan; Bossek, Jakob; Pohl, Janina; Seiler, Moritz; Trautmann, Heike; Kerschke, Pascal (Proceedings of the 16$^th$ ACM/SIGEVO Conference on Foundations of genetic Algorithms (FOGA XVI))
Classic automated algorithm selection (AS) for (combinatorial) optimization problems heavily relies on so-called instance features, i.e., numerical characteristics of the problem at hand ideally extracted with computationally low-demanding routines. For the traveling salesperson problem (TSP) a plethora of features have been suggested. Most of these features are, if at all, only normalized imprecisely raising the issue of feature values being strongly affected by the instance size. Such artifacts may have detrimental effects on algorithm selection models. We propose a normalization for two feature groups which stood out in multiple AS studies on the TSP: (a) features based on a minimum spanning tree (MST) and (b) a k-nearest neighbor graph (NNG) transformation of the input instance. To this end we theoretically derive minimum and maximum values for properties of MSTs and k-NNGs of Euclidean graphs. We analyze the differences in feature space between normalized versions of these features and their unnormalized counterparts. Our empirical investigations on various TSP benchmark sets point out that the feature scaling succeeds in eliminating the effect of the instance size. Eventually, a proof-of-concept AS-study shows promising results: models trained with normalized features tend to outperform those trained with the respective vanilla features.

Multi^3: Optimizing Multimodal Single-Objective Continuous Problems in the Multi-Objective Space by Means of Multiobjectivization - Aspar, Pelin; Kerschke, Pascal; Steinhoff, Vera; Trautmann, Heike; Grimme, Christian (Evolutionary Multi-Criterion Optimization: 11$^th$ International Conference, EMO 2021, Shenzhen, China, March 28–31, 2021, Proceedings)
In this work we examine the inner mechanisms of the recently developed sophisticated local search procedure SOMOGSA. This method solves multimodal single-objective continuous optimization problems by first expanding the problem with an additional objective (e.g., a sphere function) to the bi-objective space, and subsequently exploiting local structures and ridges of the resulting landscapes. Our study particularly focusses on the sensitivity of this multiobjectivization approach w.r.t. (i) the parametrization of the artificial second objective, as well as (ii) the position of the initial starting points in the search space. As SOMOGSA is a modular framework for encapsulating local search, we integrate Gradient and Nelder-Mead local search (as optimizers in the respective module) and compare the performance of the resulting hybrid local search to their original single-objective counterparts. We show that the SOMOGSA framework can significantly boost local search by multiobjectivization. Combined with more sophisticated local search and metaheuristics this may help in solving highly multimodal optimization problems in future.

What Is It About Humanity That We Can’t Give Away To Intelligent Machines? A European Perspective - Coombs, Crispin; Stacey, Patrick; Kawalek, Peter; Simeonova, Boyka; Becker, Jörg; Bergener, Katrin; Carvalho, João Álvaro; Fantinato, Marcelo; Garmann-Johnsen, Niels F.; Grimme, Christian; Stein, Armin; Trautmann, Heike (International Journal of Information Management)
One of the most significant recent technological developments concerns the development and implementation of ‘intelligent machines’ that draw on recent advances in artificial intelligence (AI) and robotics. However, there are growing tensions between human freedoms and machine controls. This article reports the findings of a workshop that investigated the application of the principles of human freedom throughout intelligent machine development and use. Forty IS researchers from ten different countries discussed four contemporary AI and humanity issues and the most relevant IS domain challenges. This article summarizes their experiences and opinions regarding four AI and humanity themes: Crime & conflict, Jobs, Attention, and Wellbeing. The outcomes of the workshop discussions identify three attributes of humanity that need preservation: a critique of the design and application of AI, and the intelligent machines it can create; human involvement in the loop of intelligent machine decision-making processes; and the ability to interpret and explain intelligent machine decision-making processes. The article provides an agenda for future AI and humanity research.

Towards Feature-Free Automated Algorithm Selection for Single-Objective Continuous Black-Box Optimization - Prager, Raphael Patrick; Vinzent Seiler, Moritz; Trautmann, Heike; Kerschke, Pascal (2021 IEEE Symposium Series on Computational Intelligence (SSCI))
We propose a novel method for automated algorithm selection in the domain of single-objective continuous black-box optimization. In contrast to existing methods, we use convolutional neural networks as the selection apparatus which bases its decision on a so-called ‘fitness map’. This fitness map is a 2D representation of a two dimensional search space where different gray scales indicate the quality of found solutions in certain areas. Our devised approach uses a modular CMA-ES framework which offers the option to create the conventional CMA-ES, CMA-ES with the alternate step-size adaptation and many other variants proposed over the years. In total, 4 608 different configurations are possible where most configurations are of complementary nature. In this proof-of-concept work, we consider a subset of 32 possible configurations. The developed method is evaluated against an excerpt of BBOB functions and its performance is compared against baselines that are commonly used in automated algorithm selection - the best standalone algorithm (configuration) and the best obtainable sequence of configurations. While the results indicate that the use of the fitness map is not superior on every benchmark problem, it indubitably shows its merit on more hard-to-solve problems. This offers a promising perspective for generalizing to other types of optimization problems and problem domains.

RP-Mod & RP-Crowd: Moderator- and Crowd-Annotated German News Comment Datasets - Assenmacher, Dennis; Niemann, Marco; Müller, Kilian; Seiler, Moritz V.; Riehle, Dennis M.; Trautmann, Heike (Proceedings of the Neural Information Processing Systems Track on Datasets and Benchmarks 1 (NeurIPS Datasets and Benchmarks 2021))
Abuse and hate are penetrating social media and many comment sections of news media companies. These platform providers invest considerable efforts to mod- erate user-generated contributions to prevent losing readers who get appalled by inappropriate texts. This is further enforced by legislative actions, which make non-clearance of these comments a punishable action. While (semi-)automated solutions using Natural Language Processing and advanced Machine Learning techniques are getting increasingly sophisticated, the domain of abusive language detection still struggles as large non-English and well-curated datasets are scarce or not publicly available. With this work, we publish and analyse the largest annotated German abusive language comment datasets to date. In contrast to existing datasets, we achieve a high labelling standard by conducting a thorough crowd-based an- notation study that complements professional moderators’ decisions, which are also included in the dataset. We compare and cross-evaluate the performance of baseline algorithms and state-of-the-art transformer-based language models, which are fine-tuned on our datasets and an existing alternative, showing the usefulness for the community.

Gender and Authority – The Entanglement of Two Concepts in High Medieval Historiography - Foerster, Anne (Geschlecht macht Herrschaft – Interdisziplinäre Studien zu vormoderner Macht und Herrschaft / Gender Power Sovereignty – Interdisciplinary Studies on Premodern Power)

Die Witwenschaft kinderloser Königinnen im Hochmittelalter - Foerster, Anne (Kinderlosigkeit im Mittelalter)

Erklärvideos in der Sprachwissenschaft – Sprache-Bild-Bezüge und ihr Einfluss auf den Lernerfolg (die hochschullehre – Jahrgang 7-2021)

A Database for Research on Detection and Enhancement of Speech Transmitted over HF links - Heitkaemper, Jens; Schmalenstroeer, Joerg; Ion, Valentin; Haeb-Umbach, Reinhold (Speech Communication; 14th ITG-Symposium)

How entrepreneur’s leadership behavior and demographics shape applicant attraction to new ventures: the role of stereotypes - Hubner-Benz, Sylvia; Rudic, Biljana; Baum, Matthias (The International Journal of Human Resource Management)
Keywords: Management of Technology and Innovation; Organizational Behavior and Human Resource Management; Strategy and Management; Business and International Management; Industrial relations

An Asia-centric approach to team innovation: Cultural differences in exploration and exploitation behavior - Hubner-Benz, Sylvia; Frese, Michael; Song, Zhaoli; Tripathi, Neha; Kaschner, Tamara; Le Kong, Xing (Journal of Business Research)
Keywords: Marketing

Introduction - Jacob, Joachim; Süßmann, Johannes (The Reception of Antiquity in the Age of Enlightenment. English Edition ed. by Christina C. Harker. Translated by Duncan Alexander Smart)

Investigating students' processes of noticing and interpreting syntactic language features in word problem solving through eye-tracking - Dröse, Jennifer; Prediger, S.; Neugebauer, P.; Danhier, R. D.; Mertins, B. (International Electronic Journal of Mathematics Education, 16(1), em0625)

Identifying obstacles is not enough for everybody – Differential efficacy of an intervention fostering fifth graders’ comprehension for word problems - Dröse, Jennifer; Prediger, S. (Studies in Educational Evaluation, 68 (100953))

Prokrastination bei Studierenden verringern durch Anwendung eines Ratgebers im Gruppensetting - Korsmeier, Teresa; Bobe, Julia; Klingsieck, Katrin B. (Zeitschrift für Beratung und Studium)

"Welcome to Night Vale" und/mit Derrida: Lernen, mit den Gespenstern zu leben? - Spener, Anna Maria (Literatur und das Böse. Beiträge des 10. Studierendenkongress Komparatistik)

"Meine Trauer war (k)eine Krankheit"? Achronologisches Erzählen einer anhaltenden Trauerstörung in Olga Grjasnowas "Der Russe ist einer, der Birken liebt" - Spener, Anna Maria (Anafora. Zeitschrift für Literaturwissenschaft)

A longitudinal analysis of the reciprocal relationship between academic procrastination, study satisfaction, and dropout intentions in higher education - Scheunemann, Anne; Schnettler, Theresa; Bobe, Julia; Fries, Stefan; Grunschel, Carola (European Journal of Psychology of Education)
Abstract Student dropout is a multi-causal process. Different theoretical models on student dropout consider dysfunctional study behavior (e.g., academic procrastination) and low study satisfaction as possible determinants of students’ dropout intentions during their university studies. However, these models neglect contemporary conceptualizations that assume reverse relationships between dropout intentions and other determinants of the dropout process. Until now, empirical evidence on these assumptions is scant. The present three-wave longitudinal study explored the reciprocal relationships between academic procrastination, study satisfaction, and dropout intentions over one semester. To this end, we used data of N = 326 undergraduate students enrolled in mathematics and law. Our latent cross-lagged panel model replicated existing empirical cross-sectional findings between the variables (i.e., academic procrastination, study satisfaction, and dropout intentions). Regarding the longitudinal relations, as expected, the cross-lagged effects showed that higher dropout intentions significantly related to subsequent higher academic procrastination and lower study satisfaction. Unexpectedly, academic procrastination did not significantly relate to subsequent dropout intentions. Additionally, higher study satisfaction significantly associated with subsequent higher dropout intentions—possibly due to unfulfilled expectations. Further, higher study satisfaction significantly related to subsequent higher procrastination—possibly due to more confidence among satisfied students. Our results broaden the view on dropout intentions as part of the dynamic interplay of student dropout determinants and the need to refine dropout models’ assumptions accordingly. Practically, realistic expectations seem important to reduce dropout intentions. Further, student counselors should have a closer look at the reasons for academic procrastination to develop individual solutions for this dysfunctional behavior.
Keywords: Developmental and Educational Psychology; Education

Digitales Praxissemester - kann das überhaupt gut gehen? - Göddertz, Nina (Care Work in der gesellschaftlichen Transformation. Beschäftigung, Bildung, Fachdidaktik)
Marianne Friese/Rita Braches-Chyrek Einführung Marianne Friese Care Work im Spannungsfeld gesellschaftlicher Transformation. Systemische Widersprüche und Entwicklungsperspektiven Berufliche Bildung und Beschäftigungssysteme Denise Becka und Michaela Evans Wohlfahrtsproduktion und Care im digitalen Wandel: Perspektiven für Beruflichkeit in der Pflege Heidrun Herzberg und Peter Alheit Zur Akzeptanz des Konzepts „Community Nurse" im Land Brandenburg: Eine qualitative Vorstudie Karin Reiber, Jan Braun und Jutta Mohr Berufliche Bildung in der Domäne Pflege zwischen Anforderungen des Beschäftigungssystems und individueller berufsbiografischer Entwicklung Philipp Struck Entwicklungs- und Verbesserungsperspektiven für berufliche (Aus-)Bildungsprozesse im Gesundheitswesen Rita Braches-Chyrek Soziale Arbeit: Ausbildung und Beschäftigung Julia Kastrup und Alexandra Brutzer Hauswirtschaft in Zeiten von Corona - Ergebnisse einer Interviewstudie mit Hauswirtschaftlichen Fachkräften Akademische Bildung und Weiterbildung Anna Bobe, Anke Karber und Tobias Moock Theorie und Praxis in sozialpädagogischen Bildungsgängen - Erste Strukturierungsansätze vielfältiger Verhältnisse Manuela Liebig, Mirjam Chris und Annemarie Marx „Am Ball bleiben" - Sensibilisierung für aktuelle Herausforderungen der sozialpädagogischen Praxis durch Arbeitsanalysen im Lehramtsstudium für berufliche Schulen Anja Walter, Martin Fritzenwanker, Martin Karstädt Von Berufsfeldanalysen zum Unterricht - empirisches Material für die Bildungspraxis im Berufsfeld Gesundheit und Pflege nutzen Nina Göddertz „Digitales Praxissemester - kann das überhaupt gut gehen?" - Reflexionen von Lehramtsstudierenden vor und während des Praxissemesters in Zeiten der Covid-19-Pandemie Stephanie Spanu Systemrelevant(e) ausbilden. Berufliches Lehramt, Fachrichtung Sozialpädagogik und die berufliche Bildung: Der Fachkräftemangel als gesellschaftliche Aufgabe Julia Kastrup, Birgit Peuker, Marie Nölle-Krug und Simon Vollmer Gemeinsam innovativ! - Transformative Themenfelder in der lehramtsbezogenen Ausbildung der beruflichen Fachrichtung Ernährung- und Hauswirtschaft standortübergreifend lehren und lernen Ursula Walkenhorst, Annika Lara Schwarze Digitale Transformation in der Hochschullehre - Chancen und Grenzen für die Gesundheitsberufe Dana Bergmann und Astrid Seltrecht Weiterbildungsordnungsarbeit für Pflegeberufe Claudia Schepers, Johanna Krawietz und Jella Fuchs Kollegiale Beratung für die Kitteltasche
Keywords: Modernisierung personenbezogener Dienstleistungsberufe Aktueller Forschungsstand; Best Practice und Desiderata

A Comparison and Combination of Unsupervised Blind Source Separation Techniques - Boeddeker, Christoph; Rautenberg, Frederik; Haeb-Umbach, Reinhold (ITG Conference on Speech Communication)
Unsupervised blind source separation methods do not require a training phase and thus cannot suffer from a train-test mismatch, which is a common concern in neural network based source separation. The unsupervised techniques can be categorized in two classes, those building upon the sparsity of speech in the Short-Time Fourier transform domain and those exploiting non-Gaussianity or non-stationarity of the source signals. In this contribution, spatial mixture models which fall in the first category and independent vector analysis (IVA) as a representative of the second category are compared w.r.t. their separation performance and the performance of a downstream speech recognizer on a reverberant dataset of reasonable size. Furthermore, we introduce a serial concatenation of the two, where the result of the mixture model serves as initialization of IVA, which achieves significantly better WER performance than each algorithm individually and even approaches the performance of a much more complex neural network based technique.

Convolutive Transfer Function Invariant SDR Training Criteria for Multi-Channel Reverberant Speech Separation - Boeddeker, Christoph; Zhang, Wangyou; Nakatani, Tomohiro; Kinoshita, Keisuke; Ochiai, Tsubasa; Delcroix, Marc; Kamo, Naoyuki; Qian, Yanmin; Haeb-Umbach, Reinhold (ICASSP 2021 - 2021 IEEE International Conference on Acoustics, Speech and Signal Processing (ICASSP))

Open Range Pitch Tracking for Carrier Frequency Difference Estimation from HF Transmitted Speech - Schmalenstroeer, Joerg; Heitkaemper, Jens; Ullmann, Joerg; Haeb-Umbach, Reinhold (29th European Signal Processing Conference (EUSIPCO))

Rezension von: Jörg van Norden, Thomas Must, Lars Deile, Peter Riedel, Susan Krause und Wanda Schürenberg (Hgg.): Geschichtsdidaktische Grundbegriffe. Ein Bilderbuch für Studium, Lehre und Beruf. Hannover 2020 - Hartung, Olaf (H-Soz-Kult)

Geometry calibration in wireless acoustic sensor networks utilizing DoA and distance information - Gburrek, Tobias; Schmalenstroeer, Joerg; Haeb-Umbach, Reinhold (EURASIP Journal on Audio, Speech, and Music Processing)
Due to the ad hoc nature of wireless acoustic sensor networks, the position of the sensor nodes is typically unknown. This contribution proposes a technique to estimate the position and orientation of the sensor nodes from the recorded speech signals. The method assumes that a node comprises a microphone array with synchronously sampled microphones rather than a single microphone, but does not require the sampling clocks of the nodes to be synchronized. From the observed audio signals, the distances between the acoustic sources and arrays, as well as the directions of arrival, are estimated. They serve as input to a non-linear least squares problem, from which both the sensor nodes’ positions and orientations, as well as the source positions, are alternatingly estimated in an iterative process. Given one set of unknowns, i.e., either the source positions or the sensor nodes’ geometry, the other set of unknowns can be computed in closed-form. The proposed approach is computationally efficient and the first one, which employs both distance and directional information for geometry calibration in a common cost function. Since both distance and direction of arrival measurements suffer from outliers, e.g., caused by strong reflections of the sound waves on the surfaces of the room, we introduce measures to deemphasize or remove unreliable measurements. Additionally, we discuss modifications of our previously proposed deep neural network-based acoustic distance estimator, to account not only for omnidirectional sources but also for directional sources. Simulation results show good positioning accuracy and compare very favorably with alternative approaches from the literature.

Iterative Geometry Calibration from Distance Estimates for Wireless Acoustic Sensor Networks - Gburrek, Tobias; Schmalenstroeer, Joerg; Haeb-Umbach, Reinhold (ICASSP 2021 - 2021 IEEE International Conference on Acoustics, Speech and Signal Processing (ICASSP))

On Source-Microphone Distance Estimation Using Convolutional Recurrent Neural Networks - Gburrek, Tobias; Schmalenstroeer, Joerg; Haeb-Umbach, Reinhold (Speech Communication; 14th ITG-Symposium)

Online Estimation of Sampling Rate Offsets in Wireless Acoustic Sensor Networks with Packet Loss - Chinaev, Aleksej; Enzner, Gerald; Gburrek, Tobias; Schmalenstroeer, Joerg (29th European Signal Processing Conference (EUSIPCO))

Seelsorge der Geschichte? Konfessionelle Geschichtspolitik im 17. Jahrhundert am Beispiel der Monumenta Paderbornensia Ferdinands von Fürstenberg - Moritz, Tilman (Katholische Konfessionalisierung in Paderborn? Religiöse Prozesse in der Frühen Neuzeit)

Forschungsperspektiven - Moritz, Tilman; Kopp, Stefan; Priesching, Nicole (Katholische Konfessionalisierung in Paderborn? Religiöse Prozesse in der Frühen Neuzeit)

Zum Paradigma der Konfessionalisierung - Moritz, Tilman; Kopp, Stefan; Priesching, Nicole (Katholische Konfessionalisierung in Paderborn? Religiöse Prozesse in der Frühen Neuzeit)

A. Seidler, I. Monok (Hgg.): Reformation und Bücher. Zentren der Ideen – Zentren der Buchproduktion. Wiesbaden 2020 - Moritz, Tilman (sehepunkte)

Das Commentariolum Ferdinands von Fürstenberg – eine lateinisch-deutsche Synopse - Moritz, Tilman (Katholische Konfessionalisierung in Paderborn? Religiöse Prozesse in der Frühen Neuzeit)

Katholische Konfessionalisierung in Paderborn? Religiöse Prozesse in der Frühen Neuzeit

Max Schulze vs. Joana Dahlhoff - Schulze, Max (Joana Dahlhoff: Recherche patiente)

Shared Leadership: Neue Studien für die Unternehmenspraxis - Krebs, Benjamin; Kabst, Rüdiger (PERSONALquartely)

HR-Manager als Intrapreneure - Wach, Bernhard; Krebs, Benjamin; Kabst, Rüdiger (HR-Trends 2021)

Contrastive Predictive Coding Supported Factorized Variational Autoencoder for Unsupervised Learning of Disentangled Speech Representations - Ebbers, Janek; Kuhlmann, Michael; Cord-Landwehr, Tobias; Haeb-Umbach, Reinhold (Proceedings of the IEEE International Conference on Acoustics, Speech and Signal Processing (ICASSP))
In this work we address disentanglement of style and content in speech signals. We propose a fully convolutional variational autoencoder employing two encoders: a content encoder and a style encoder. To foster disentanglement, we propose adversarial contrastive predictive coding. This new disentanglement method does neither need parallel data nor any supervision. We show that the proposed technique is capable of separating speaker and content traits into the two different representations and show competitive speaker-content disentanglement performance compared to other unsupervised approaches. We further demonstrate an increased robustness of the content representation against a train-test mismatch compared to spectral features, when used for phone recognition.

Human Factors in Secure Software Development - Acar, Yasemin

A Large-Scale Interview Study on Information Security in and Attacks against Small and Medium-sized Enterprises - Huaman, Nicolas; von Skarczinski, Bennet; Stransky, Christian; Wermke, Dominik; Acar, Yasemin; Dreißigacker, Arne; Fahl, Sascha (30th USENIX Security Symposium, USENIX Security 2021, August 11-13, 2021)

Why Eve and Mallory Still Love Android: Revisiting TLS (In)Security in Android Applications - Oltrogge, Marten; Huaman, Nicolas; Amft, Sabrina; Acar, Yasemin; Backes, Michael; Fahl, Sascha (30th USENIX Security Symposium, USENIX Security 2021, August 11-13, 2021)

Passivität als Widerstand gegen die Macht der Verhältnisse? Melvilles Bartleby, the scrivener aus literaturwissenschaftlicher und ökonomischer Perspektive - Öhlschläger, Claudia; Schneider, Martin (Komparatistik heute)

Happy clappy heile Welt? Wie angesichts von Krisen und Katastrophen eine schöne Welt besungen werden kann - Neumann, Anna (Musik als Lebensmittel. Kulturwissenschaftlich-theologische Rationen für ein Jahr)

This is my Fight Song - Neumann, Anna; Katharina, Kammeyer; Vera, Uppenkamp (Musk als Lebensmittel)

Keller, Raabe, Fontane: ›nichts für den Durchschnittsleser‹. Miszellane Lektüren, ›imaginäre Leser‹ und Kanonisierungsprozesse in der Literaturkritik der zeitgenössischen Presse - Gretz, Daniela (Miszellanes Lesen. Interferenzen zwischen medialen Formaten, Romanstrukturen und Lektürepraktiken im 19. Jahrhundert)

Miszellanes Lesen. Interferenzen zwischen medialen Formaten, Romanstrukturen und Lektürepraktiken im 19. Jahrhundert

Mit Aufgaben im inklusiven Mathematikunterricht professionell umgehen - Erkenntnisse einer Interviewstudie mit Lehrpersonen der Sekundarstufe - Häsel-Weide, Uta; Seitz, Simone; Wallner, Melina; Wilke, Yannik; Heckmann, Lara (QfI - Qualifizierung für Inklusion. Online-Zeitschrift zur Forschung über Aus-, Fort- und Weiterbildung pädagogischer Fachkräfte)

Conceptualiziation processes of 6th graders for rotational symmetry - Hattermann, Mathias; Häsel-Weide, Uta; Wallner, Melina (Proceedings of the 44th Conference of the International Group for the Psychology of Mathematics Education)

Zusammenhang zwischen familiären Lebenssituationen und Werteähnlichkeiten in der Eltern-Kind-Beziehung im Erwachsenenalter. - Hoellger, Christian; Sommer, Sabrina; Buhl, Heike M. (Zeitschrift für Soziologie der Erziehung und Sozialisation)

Bifurcation preserving discretisations of optimal control problems - Offen, Christian; Ober-Blöbaum, Sina
The first order optimality conditions of optimal control problems (OCPs) can be regarded as boundary value problems for Hamiltonian systems. Variational or symplectic discretisation methods are classically known for their excellent long term behaviour. As boundary value problems are posed on intervals of fixed, moderate length, it is not immediately clear whether methods can profit from structure preservation in this context. When parameters are present, solutions can undergo bifurcations, for instance, two solutions can merge and annihilate one another as parameters are varied. We will show that generic bifurcations of an OCP are preserved under discretisation when the OCP is either directly discretised to a discrete OCP (direct method) or translated into a Hamiltonian boundary value problem using first order necessary conditions of optimality which is then solved using a symplectic integrator (indirect method). Moreover, certain bifurcations break when a non-symplectic scheme is used. The general phenomenon is illustrated on the example of a cut locus of an ellipsoid.
Keywords: optimal control; catastrophe theory; bifurcations; variational methods; symplectic integrators

Learning ODE Models with Qualitative Structure Using Gaussian Processes - Ridderbusch, Steffen; Offen, Christian; Ober-Blöbaum, Sina; Goulart, Paul (2021 60th IEEE Conference on Decision and Control (CDC))

Multi-objective minimum time optimal control for low-thrust trajectory design - Vertovec, Nikolaus; Ober-Blöbaum, Sina; Margellos, Kostas
We propose a reachability approach for infinite and finite horizon multi-objective optimization problems for low-thrust spacecraft trajectory design. The main advantage of the proposed method is that the Pareto front can be efficiently constructed from the zero level set of the solution to a Hamilton-Jacobi-Bellman equation. We demonstrate the proposed method by applying it to a low-thrust spacecraft trajectory design problem. By deriving the analytic expression for the Hamiltonian and the optimal control policy, we are able to efficiently compute the backward reachable set and reconstruct the optimal trajectories. Furthermore, we show that any reconstructed trajectory will be guaranteed to be weakly Pareto optimal. The proposed method can be used as a benchmark for future research of applying reachability analysis to low-thrust spacecraft trajectory design.

Fractional Damping Through Restricted Calculus of Variations - Jiménez, F.; Ober-Blöbaum, Sina (Nichtlineare Sci 31)

Der steinige Weg vom Wissen zum Können: Zum schwierigen Verhältnis von Theorie und Praxis bei der Betreuung zukünftiger Geschichtslehrkräfte in Langzeitpraktika - Hartung, Olaf; Krebs, Alexandra; Fastlabend-Vargas, Daniel; Meyer-Hamme, Johannes (Theorie und Praxis in der Lehrerbildung.Verhältnisbestimmungen aus der Perspektive von Fachdidaktiken)

„Da öffnet er ihnen das Verständnis, sodass sie die Schriften verstanden“ (Lk 24,45) - Breuer, Saskia Rebecca (Der Dom. Katholisches Magazin im Erzbistum Paderborn)

The Rise of Interactional Multimodality in Human-Computer Interaction - Klowait, Nils; Ерофеева, Мария Александровна (The monitoring of public opinion economic&social changes)
The field of human-computer interaction (HCI) investigates the intersection between the design of devices and users. From an early focus on interaction modeling based on psychological experiments, the field has since experienced a shift towards the study of how actual humans interact with autonomous devices. The field became conductive to ethnographic, observational and videographic studies of human-device interaction. Conversation-analytic HCI became possible. That said, this new wave of researchers was never truly able to dethrone the psychological common sense of the field. With recent developments in both the technical-sensorial capabilities and outward actuational range of embodied virtual agents, the field of HCI has once again returned to the question of the sequential unfolding of the interaction between users and intelligent agents, and the multimodal interactional repertoire that is deployed throughout. This review will highlight the situational orientation of high-impact research in the field, and relate it to the cotemporaneous development of ethnomethodological and conversation analytic frameworks. Acknowledgments. The article was prepared in the framework of a research grant funded by the Ministry of Science and Higher Education of the Russian Federation (grant ID: 075-15-2020-908). The article was prepared in cooperation with the Sber (ex. – Sberbank’s) Gamification Lab.
Keywords: Economics; Econometrics and Finance (miscellaneous); Sociology and Political Science

Home-Office. Kulturelle Formationen häuslicher Arbeit - Miggelbrink, Monique; Bartz, Christina (Selbstbehältnisse. Orte und Gegenstände der Aufbewahrung von Subjektivität)

Forschungsfelder für Künstliche Intelligenz in der strategischen Produktplanung - Ködding, Patrick; Dumitrescu, Roman (Digitalisisierung souverän gestalten)

Selective area growth of cubic gallium nitride on silicon (001) and 3C-silicon carbide (001) - Meier, F.; Protte, M.; Baron, E.; Feneberg, M.; Goldhahn, R.; Reuter, Dirk; As, Donat Josef (AIP Advances)

“Seeing Is Believing”—In-Depth Analysis by Co-Imaging of Periodically-Poled X-Cut Lithium Niobate Thin Films - Reitzig, Sven; Rüsing, Michael; Zhao, Jie; Kirbus, Benjamin; Mookherjea, Shayan; Eng, Lukas M. (Crystals)
Nonlinear and quantum optical devices based on periodically-poled thin film lithium niobate (PP-TFLN) have gained considerable interest lately, due to their significantly improved performance as compared to their bulk counterparts. Nevertheless, performance parameters such as conversion efficiency, minimum pump power, and spectral bandwidth strongly depend on the quality of the domain structure in these PP-TFLN samples, e.g., their homogeneity and duty cycle, as well as on the overlap and penetration depth of domains with the waveguide mode. Hence, in order to propose improved fabrication protocols, a profound quality control of domain structures is needed that allows quantifying and thoroughly analyzing these parameters. In this paper, we propose to combine a set of nanometer-to-micrometer-scale imaging techniques, i.e., piezoresponse force microscopy (PFM), second-harmonic generation (SHG), and Raman spectroscopy (RS), to access the relevant and crucial sample properties through cross-correlating these methods. Based on our findings, we designate SHG to be the best-suited standard imaging technique for this purpose, in particular when investigating the domain poling process in x-cut TFLNs. While PFM is excellently recommended for near-surface high-resolution imaging, RS provides thorough insights into stress and/or defect distributions, as associated with these domain structures. In this context, our work here indicates unexpectedly large signs for internal fields occurring in x-cut PP-TFLNs that are substantially larger as compared to previous observations in bulk LN.
Keywords: Inorganic Chemistry; Condensed Matter Physics; General Materials Science; General Chemical Engineering

Photoconduction of Polar and Nonpolar Cuts of Undoped Sr0.61Ba0.39Nb2O6 Single Crystals - Beyreuther, Elke; Ratzenberger, Julius; Roeper, Matthias; Kirbus, Benjamin; Rüsing, Michael; Ivleva, Liudmila I.; Eng, Lukas M. (Crystals)
In the last two decades, variably doped strontium barium niobate (SBN) has attracted a lot of scientific interest mainly due to its specific non-linear optical response. Comparably, the parental compound, i.e., undoped SBN, appears to be less studied so far. Here, two different cuts of single-crystalline nominally pure strontium barium niobate in the composition Sr0.61Ba0.39Nb2O6 (SBN61) are comprehensively studied and analyzed with regard to their photoconductive responses. We present conductance measurements under systematically varied illumination conditions along either the polar z-axis or perpendicular to it (x-cut). Apart from a pronounced photoconductance (PC) already under daylight and a large effect upon super-bandgap illumination in general, we observe (i) distinct spectral features when sweeping the excitation wavelength over the sub-bandgap region as then discussed in the context of deep and shallow trap states, (ii) extremely slow long-term relaxation for both light-on and light-off transients in the range of hours and days, (iii) a critical dependence of the photoresponse on the pre-illumination history of the sample, and (iv) a current–voltage hysteresis depending on both the illumination and the electrical-measurement conditions in a complex manner.
Keywords: Inorganic Chemistry; Condensed Matter Physics; General Materials Science; General Chemical Engineering

Tricyanidoferrates(−IV) and Ruthenates(−IV) with Non‐Innocent Cyanido Ligands - Jach, Franziska; Wagner, Frank R.; Amber, Zeeshan H.; Rüsing, Michael; Hunger, Jens; Prots, Yurii; Kaiser, Martin; Bobnar, Matej; Jesche, Anton; Eng, Lukas M.; Ruck, Michael; Höhn, Peter (Angewandte Chemie International Edition)
Exceptionally electron-rich, nearly trigonal-planar tricyanidometalate anions [Fe(CN)3]7− and [Ru(CN)3]7− were stabilized in LiSr3[Fe(CN)3] and AE3.5[M(CN)3] (AE=Sr, Ba; M=Fe, Ru). They are the first examples of group 8 elements with the oxidation state of −IV. Microcrystalline powders were obtained by a solid-state route, single crystals from alkali metal flux. While LiSr3[Fe(CN)3] crystallizes in P63/m, the polar space group P63 with three-fold cell volume for AE3.5[M(CN)3] is confirmed by second harmonic generation. X-ray diffraction, IR and Raman spectroscopy reveal longer C−N distances (124–128 pm) and much lower stretching frequencies (1484–1634 cm−1) than in classical cyanidometalates. Weak C−N bonds in combination with strong M−C π-bonding is a scheme also known for carbonylmetalates. Instead of the formal notation [Fe−IV(CN−)3]7−, quantum chemical calculations reveal non-innocent intermediate-valent CN1.67− ligands and a closed-shell d10 configuration for Fe, that is, Fe2−.
Keywords: General Chemistry; Catalysis

Quantifying the coherent interaction length of second-harmonic microscopy in lithium niobate confined nanostructures - Amber, Zeeshan H.; Kirbus, Benjamin; Eng, Lukas M.; Rüsing, Michael (Journal of Applied Physics)
Thin-film lithium niobate (TFLN) in the form of x- or z-cut lithium-niobate-on-insulator has attracted considerable interest as a very promising and novel platform for developing integrated optoelectronic (nano)devices and exploring fundamental research. Here, we investigate the coherent interaction length lc of optical second-harmonic generation (SHG) microscopy in such samples, that are purposely prepared into a wedge shape, in order to elegantly tune the geometrical confinement from bulk thicknesses down to approximately 50 nm. SHG microscopy is a very powerful and non-invasive tool for the investigation of structural properties in the biological and solid-state sciences, especially for visualizing and analyzing ferroelectric domains and domain walls. However, unlike in bulk lithium niobate (LN), SHG microscopy in TFLN is impacted by interfacial reflections and resonant enhancement, both of which rely on film thickness and substrate material. In this paper, we show that the dominant SHG contribution measured on TFLN in backreflection is the co-propagating phase-matched SHG signal and not the counter-propagating SHG portion as is the case for bulk LN samples. Moreover, lc depends on the incident pump laser wavelength (sample dispersion) but also on the numerical aperture of the focussing objective in use. These experimental findings on x- and z-cut TFLN are excellently backed up by our advanced numerical simulations.
Keywords: General Physics and Astronomy

Potassium Ion Conductivity in the Cubic Labyrinth of a Piezoelectric, Antiferromagnetic Oxoferrate(III) Tellurate(VI) - Albrecht, Ralf; Hoelzel, Markus; Beccard, Henrik; Rüsing, Michael; Eng, Lukas; Doert, Thomas; Ruck, Michael (Chemistry – A European Journal)
Orange-colored crystals of the oxoferrate tellurate K12+6xFe6Te4−xO27 [x=0.222(4)] were synthesized in a potassium hydroxide hydroflux with a molar water–base ratio n(H2O)/n(KOH) of 1.5 starting from Fe(NO3)3 ⋅ 9H2O, TeO2 and H2O2 at about 200 °C. By using (NH4)2TeO4 instead of TeO2, a fine powder consisting of microcrystalline spheres of K12+6xFe6Te4−xO27 was obtained. K12+6xFe6Te4−xO27 crystallizes in the acentric cubic space group Iurn:x-wiley:09476539:media:chem202102464:chem202102464-math-0001 3d. [FeIIIO5] pyramids share their apical atoms in [Fe2O9] groups and two of their edges with [TeVIO6] octahedra to form an open framework that consists of two loosely connected, but not interpenetrating, chiral networks. The flexibility of the hinged oxometalate network manifests in a piezoelectric response similar to that of LiNbO3.The potassium cations are mobile in channels that run along the <111> directions and cross in cavities acting as nodes. The ion conductivity of cold-pressed pellets of ball-milled K12+6xFe6Te4−xO27 is 2.3×10^(−4) S ⋅ cm^(−1) at room temperature. Magnetization measurements and neutron diffraction indicate antiferromagnetic coupling in the [Fe2O9] groups.
Keywords: General Chemistry; Catalysis; Organic Chemistry

Quantifying the refractive index of ferroelectric domain walls in periodically poled LiNbO3 single crystals by polarization-sensitive optical coherence tomography - Golde, Jonas; Rüsing, Michael; Rix, Jan; Eng, Lukas M.; Koch, Edmund (Optics Express)
Domain walls (DWs) in ferroelectric (FE) and multiferroic materials possess an ever-growing potential as integrated functional elements, for instance in optoelectronic nanodevices. Mandatory, however, is the profound knowledge of the local-scale electronic and optical properties, especially at DWs that are still incompletely characterized to date. Here, we quantify the refractive index of individual FE DWs in periodically-poled LiNbO 3 (PPLN) single crystals. When applying polarization-sensitive optical coherence tomography (PS-OCT) at 1300 nm using circular light polarization, we are able to probe the relevant electro-optical properties close to and at the DWs, including also their ordinary and extraordinary contributions. When comparing to numerical calculations, we conclude that the DW signals recorded for ordinary and extraordinary polarization stem from an increased refractive index of at least Δn > 2·10 −3 that originates from a tiny region of < 30 nm in width. PS-OCT hence provides an extremely valuable tool to decipher and quantify subtle changes of refractive index profiles for both inorganic and biomedical nanomaterial systems.
Keywords: Atomic and Molecular Physics; and Optics

Broadband coherent anti-Stokes Raman scattering for crystalline materials - Hempel, Franz; Reitzig, Sven; Rüsing, Michael; Eng, Lukas M. (Physical Review B)
Broadband coherent anti-Stokes Raman scattering (B-CARS) has emerged in recent years as a promising chemosensitive high-speed imaging technique. B-CARS allows for the detection of vibrational sample properties in analogy to spontaneous Raman spectroscopy, but also makes electronic sample environments accessible due to its resonant excitation mechanism. Nevertheless, this technique has only gained interest in the biomedical field so far, whereas CARS investigations on solid-state materials are rare and concentrate on layered, two-dimensional materials such as graphene and hexagonal boron nitride . In this work, we discuss the specific properties of this technique when applied to single-crystalline samples, with respect to signal generation, phase matching, and selection rules in the model systems lithium niobate and lithium tantalate. Via polarized B-CARS measurements and subsequent phase retrieval, we validate the predicted selection rules, unequivocally assign the phonons of the A1(TO), E(TO) and A1(LO) branches to the detected CARS peaks, and address differences in spontaneous Raman spectroscopy concerning peak frequencies and scattering efficiencies. We thus establish this technique for future investigations of solid-state materials, specifically in the field of ferroelectric single crystals.

Mental body rotation with egocentric and object-based transformations in different postures: standing vs. balancing - Budde, Kirsten; Jöllenbeck, Thomas; Barela, José A.; Figueiredo, Gabriella A.; Weigelt, Matthias (Brazilian Journal of Motor Behavior)
BACKGROUND: Previous studies suggest better visual-spatial processing when participants are tested in postures in which dynamic stability is challenged. The question arises if this is also true for the performance in mental body-rotation tasks (MBRT). AIM: Taking the embodied cognition approach into account, the first aim of the present study was to examine the potential influence of different demands on dynamic stability for two postures (parallel stand vs. tandem stand) on solving two versions of the MBRT, inducing either an object-based or an egocentric perspective transformation strategy. The second aim was to investigate if these different demands on dynamic stability are reflected in postural sway parameters. METHOD: Thirty participants (18 females and 12 males) were tested in the two MBRTs and in a control condition. All tasks were performed while standing on a balance beam in tandem stand and in a feet parallel position on a force plate. RESULTS: The results for response time and response error revealed effects of rotation angle and task, but no effect of posture. The analyzed Center of Pressure (CoP) data revealed a reduction of body sway during the MBRT for egocentric perspective transformations. CONCLUSION: The results indicate that participants performed better for egocentric than for object-based transformations and that the egocentric transformation leads to more postural stability than the object-based.

Mental body rotation with egocentric and object-based transformations in different postures: sitting vs. standing. - Budde, Kirsten; Barela, José A; Figueiredo, Gabriella A; Weigelt, Matthias (TeaP 2021 - Abstracts of the 63rd Conference of Experimental Psychologists.)

Mechanical joining of glass fibre reinforced polymer (GFRP) through an innovative solid self-piercing rivet - Han, Daxin; Yang, Keke; Meschut, Gerson (Journal of Materials Processing Technology)
Keywords: Industrial and Manufacturing Engineering; Metals and Alloys; Computer Science Applications; Modeling and Simulation; Ceramics and Composites

A first introduction to data science education in secondary schools: Teaching and learning about data exploration with CODAP using survey data - Frischemeier, Daniel; Biehler, Rolf; Podworny, Susanne; Budde, Lea (Teaching Statistics)
Abstract In this paper, we will describe an introduction to Data Science for secondary school students. We will report on the design and implementation of an introductory unit on “Data and data detectives with CODAP” in which secondary school students used the online tool CODAP to explore real and meaningful survey data on leisure time activities and media use (so‐called JIM‐PB data) in a statistical project setting as a starting point for data science. The JIM‐PB data set served as a valuable data set that offered meaningful and exciting opportunities for data exploration for secondary school students, and CODAP proved to be a valuable tool for the first explorations of this data.
Keywords: Education; Statistics and Probability

Integration fachwissenschaftlicher und fachdidaktischer Komponenten in der Lehramtsausbildung Mathematik Grundschule am Beispiel einer Veranstaltung zur Leitidee „Daten, Häufigkeit und Wahrscheinlichkeit“ - Frischemeier, Daniel; Podworny, Susanne; Biehler, Rolf (Konzepte und Studien zur Hochschuldidaktik und Lehrerbildung Mathematik)

Zur neuen Bedeutung von Daten in Data Science und künstlicher Intelligenz - Höper, Lukas; Podworny, Susanne; Hüsing, Sven; Schulte, Carsten; Fleischer, Yannik; Biehler, Rolf; Frischemeier, Daniel; Malatyali, Hülya

When differential privacy meets NLP: The devil is in the detail - Habernal, Ivan (Proceedings of the 2021 Conference on Empirical Methods in Natural Language Processing)

Alternating Asymmetrical Phase-Shift Modulation for Full-Bridge Converters with Balanced Switching Losses to Reduce Thermal Imbalances - Rehlaender, Philipp; Unruh, Roland; Schafmeister, Frank; Böcker, Joachim (2021 IEEE Applied Power Electronics Conference and Exposition (APEC))
Phase-shift modulated full bridge converters suffer from thermal imbalances of the inverter switches. The lagging leg switches are subject to larger commutation currents compared to those of the leading leg as the transformer current reduces in the freewheeling interval. Furthermore, after this interval, the energy in the series inductance may not be large enough to achieve zero-voltage switching (ZVS) for the leading leg. Both effects result in thermal imbalances. This paper analyzes the alternating-asymmetrical phase-shift modulation to achieve balanced conduction and switching losses for all four switches while showing that this modulation is easily implemented on standard DSPs. The modulation has been implemented to LLC converters where experimental measurement results proved its effectiveness for LLC converters by reducing the temperature deviation from 6.3 K to only 0.2 K such that the peak temperature is reduced from 95 °C to 92 °C. The paper also proves that the modulation can be utilized to improve the efficiency of LLC converters operated at very low gains while simultaneously reducing the junction temperature of all four switches compared to the conventional complementary modulation. Finally, EMI implications are analyzed, which show that the modulation may be beneficial for reducing the common-mode emissions around the operating frequency.
Keywords: Phase-Shifted Full Bridge; Full-Bridge Converter; Phase-Shift Control; Phase-Shift Modulation; LLC Converter; Thermal Balancing

Geometrisches Begriffsverständnis in der Grundschule am Beispiel der Begriffe Viereck, Rechteck und Quadrat - Bruns, Julia; Unterhauser, Elisabeth; Gasteiger, Hedwig (Journal für Mathematik-Didaktik)
Zusammenfassung Zu den ersten geometrischen Begriffen, die Kinder bereits im Elementar- und Primarbereich lernen, zählen u. a. Viereck, Rechteck und Quadrat. Studien zeigen, dass Lernende bereits früh individuelle Vorstellungen, sog. individuelle Begriffskonzepte, zu diesen Begriffen aufbauen. Zwar wird die Entwicklung von Begriffsverständnis in verschiedenen mathematikdidaktischen Stufenmodellen dargestellt, diese sind jedoch generisch und beschreiben nicht explizit die Entwicklung der ersten individuellen Begriffskonzepte von Lernenden zu Viereck, Rechteck und Quadrat. Aus empirischer Sicht liegen verschiedene Studien vor, die einzelne Aspekte der individuellen Begriffskonzepte von Lernenden unterschiedlicher Altersgruppen zu diesen Begriffen ausleuchten. Um Begriffsbildungsprozesse aus empirischer Sicht detaillierter entlang der jeweils vorherrschenden individuellen Begriffskonzepte zu beschreiben, fehlen insbesondere Studien in der Grundschule, die alle vier Klassenstufen betrachten und dabei differenzierte Erkenntnisse zu verschiedenen theoretischen Indikatoren des Begriffsverständnisses liefern. Daher geht die vorliegende Studie der Frage nach, welches Verständnis der Begriffe Viereck, Rechteck und Quadrat Schülerinnen und Schüler der Jahrgangsstufen 1, 2, 3 und 4 zeigen. Dazu wurde eine Quasi-Längsschnittstudie mit N = 456 Grundschulkindern (ca. 100 pro Jahrgangsstufe) durchgeführt. Die Ergebnisse geben detaillierte Einblicke in die individuellen Begriffskonzepte der Lernenden und zeigen, dass Lernende zunehmend Eigenschaften der Figuren berücksichtigen, jedoch individuelle Begriffskonzepte über lange Zeit auch prototypisch geprägt sind. Implikationen dieser Ergebnisse für Forschung und Praxis werden diskutiert.
Keywords: Education; General Mathematics

Tocotronic - Hoffnung (2020). - Jacke, Christoph (Musik als Lebensmittel. Kulturwissenschaftlich-theologische Rationen für ein Jahr.)

Teilhabe von Eltern an schulischem Lernen mit Family-Literacy-Programmen. Langzeiteffekte von „LIFE – Lesen in Familie erleben“ auf die elterliche Unterstützung beim Lesenlernen - Bonanati, Sabrina; Gruchel, Nicole; Kurock, Ricarda; Buhl, Heike M. (Die Deutsche Schule)
Family-Literacy-Programme stellen eine gute Möglichkeit dar, Eltern in Bildungsprozesse einzubeziehen. Am Beispiel des Programms „LIFE – Lesen in Familie erleben“ wird die Wirkung auf elterliche Unterstützung beim Lesenlernen von Erstklässler*innen unter Einbezug von Eltern- und Kinderperspektive untersucht. Sowohl direkt nach dem Programm als auch ein halbes Jahr später wirkte das Programm positiv auf verschiedene Arten der Anschlusskommunikation beim gemeinsamen Lesen.
Keywords: Kooperation; Familie; Lesekompetenz; Längsschnittstudie; Intervention

Schule und außerschulische Bildungspartner an der Schnittstelle von formalen und non-formalen Bildungsprozessen - Empirische Befunde zur Kooperation und professionellen Handlungskompetenz - Limpinsel, Inga; Engemann, Mario; Neuberger, Olga; Serova, Katja; Aßmann, Sandra (Kooperation - Koordination - Kollegialität. Befunde und Diskurse zum (multi-)professionellen Zusammenwirken pädagogischer Akteur*innen an Schulen)

Lehrerkooperation und Digitalisierung - Gestaltung digital-kooperativer Arbeitsbeziehungen von Lehrkräften und ReferendarInnen am Beispiel des Schulfachs Pädagogik - Engemann, Mario; Herzig, Bardo (Fachliche Bildung und digitale Transformation - Fachdidaktische Forschung und Diskurse. Fachtagung der Gesellschaft für Fachdidaktik 2020)

Lehrerkooperation vor dem Hintergrund der Digitalisierung: Eine Untersuchung innerhalb von Fachkollegien im gymnasialen Schulfach Pädagogik - Engemann, Mario; Herzig, Bardo

When agency “fits” regardless of gender: Perceptions of applicant fit when job and organization signal male stereotypes - Dutz, Regina; Hubner-Benz, Sylvia; Peus, Claudia (Personnel Psychology)
Evaluators’ fit assessments are not only influenced by applicants’ qualities, but also by stereotypes, especially in recruitment for high‐status jobs in male‐dominated fields. The unidimensional agentic stereotype of these work contexts signals agentic job and organizational requirements (stereotypically male qualities such as achievement orientation), although the actual requirements usually also include communality (stereotypically female qualities such as interpersonal skills). In five experiments, we investigate the relevance of perceived applicant agency for perceived applicant fit, the influence of recruitment material, contextual differences, and the role of applicant gender. Our findings indicate that perceived applicant agency drives perceived person‐job and person‐organization fit in strictly male stereotyped work contexts, regardless of gender, and agentic recruitment material enhances this effect. Contrasting different contexts (high‐ with low‐status jobs and a male‐dominated with a gender‐balanced and female‐dominated field) revealed that the relevance of perceived agency increases with perceived job status, and the relevance of perceived communality decreases with the expected share of men. Although women were perceived as highly agentic in strictly male stereotyped work contexts, their need to be perceived as agentic also was higher than for men, due to the perceived lack of fit between women and high‐status jobs.
Keywords: Organizational Behavior and Human Resource Management; Applied Psychology

Narratives in entrepreneurial ecosystems: drivers of effectuation versus causation - Hubner-Benz, Sylvia; Most, Fabian; Wirtz, Jochen; Auer, Christine (Small Business Economics)
This paper introduces narratives in entrepreneurial ecosystems as drivers of effectuation vs. causation. Drawing on 43 interviews with successful players in Silicon Valley, Munich, and Singapore, we found ecosystem-specific narratives indicate what is common, appropriate, and successful in each ecosystem, and these narratives encourage either effectuation or causation. Our findings indicate that the narratives in the ecosystem in Silicon Valley facilitate effectuation, in Munich causation, and in Singapore a cautious balance of both. Our research suggests that narratives can explain mechanisms how ecosystems influence entrepreneurship: the national culture, market characteristics, available resources, and networks in an ecosystem spark ecosystem-specific narratives, which in turn shape tendencies towards effectuation and causation. Thereby, we introduce a new ecosystem-focused perspective on predictors of effectuation and causation.
Keywords: Economics and Econometrics; General Business; Management and Accounting

Weder - Noch. Was mich theologisch prägt - Schroeter-Wittke, Harald (Magazin für Theologie und Ästhetik. (https://www.theomag.de/129/hsw22.pdf))

Fehlerbearbeitung bei mathematischen Textaufgaben – Sprachliche und strategische Fehlerursachen und ihre Bearbeitung - Prediger, Susanne; Dröse, Jennifer (Lernen und Lernstörungen, 10(2))

System mit optischer Trägerverteilung - Kruse, Stephan; Scheytt, J. Christoph

Elektrooptischer Regelkreis - Kruse, Stephan; Scheytt, J. Christoph

Fälle als Reflexionsanlass im Unterricht: Theoretische und empirische Zugänge zur Fallarbeit als Methode im Schulfach Erziehungswissenschaft - Engemann, Mario; Gather, Katharina; Martin, Alexander

Neurophysiology of embodied mental rotation: Event‐related potentials in a mental rotation task with human bodies as compared to alphanumeric stimuli - Krause, Daniel; Richert, Benjamin; Weigelt, Matthias (European Journal of Neuroscience)
Abstract The present study examines if the neural signature of information processing in mental rotation tasks is moderated by stimulus characteristics (e.g., body‐related vs. non‐body‐related stimuli). In the present experiment, stimulus sets of human figures (back view; left vs. right arm abduction) and alphanumeric characters (‘R’; normal vs. mirrored view) were scrutinized with event‐related potentials (ERPs) in the electroencephalography (EEG). Participants had to judge parity between an upright (0° orientation) and a comparison stimulus (stimulus disparity; 0°, 45°, 90°, 135° or 180°). There was a main effect of stimulus disparity for the behavioural (response time and error rates), as well as for the neural data (rotation‐related negativity, RRN). The interaction of stimulus disparity and stimulus type was significant for the RRN, but not for the response time. Lower RRN amplitudes for letters indicate a more pronounced use of alternative processes (e.g., memory retrieval), which seems to be reflected in higher N350 amplitudes. Moreover, the increase of the RRN amplitude and the increase in response time as a function of disparity were positively correlated. Task differences were evident for several ERP components (i.e., N150, P150 and N250), being independent of disparity, which might reflect differences in early and late object cognition prior to the mental rotation process itself. This might be associated with the task‐dependent activation of embodied cognition processes in mental rotation tasks.
Keywords: General Neuroscience

Valence-dependent neural correlates of augmented feedback processing in extensive motor sequence learning – Part II: Predictive value of event-related potentials for behavioral adaptation and learning - Margraf, Linda; Krause, Daniel; Weigelt, Matthias (Neuroscience)
Keywords: General Neuroscience

Stimulating performance: A scoping review on transcranial electrical stimulation effects on olympic sports - Friehs, Maximilian A.; Whelan, Eric; Güldenpenning, Iris; Krause, Daniel; Weigelt, Matthias (Psychology of Sport and Exercise)
Keywords: Applied Psychology

Valence-dependent Neural Correlates of Augmented Feedback Processing in Extensive Motor Sequence Learning – Part I: Practice-related Changes of Feedback Processing - Margraf, Linda; Krause, Daniel; Weigelt, Matthias (Neuroscience)
Keywords: General Neuroscience

Die Förderung demokratischer Grundhaltungen als Teil professioneller Kompetenz angehender Lehrpersonen: Darstellung eines Forschungsvorhabens - Wehde, Janis; Bloh, Bea

Salutogenes Leitungshandeln. Ein Ansatz zur Gesundheitsförderung und Qualitätsentwicklung in der Schule. - Bloh, Bea; Wehde, Janis (Lernende Schule)

Präkonzepte von Grundschulkindern zur Zeitzeug*innenbefragung – Eine empirische Untersuchung zu Kompetenzen historischen Denkens - Diederich, Julia
Die Zeitzeug*innenbefragung gilt als kindgemäßer Zugang zur Alltags- und Zeitgeschichte. Sie charakterisiert sich sowohl als geschichtswissenschaftliche Forschungsmethode als auch Unterrichtsmethode zur Erstellung, Bearbeitung und Interpretation historischer Quellen mittels Erinnerungsinterviews zu vergangenen Erlebnissen und Erfahrungen (vgl. Michalik 2017, Schreiber 2009). Trotz einer bildungspolitischen Empfehlung der Methode der Zeitzeug*innenbefragung ab dem Anfangsunterricht des Sachunterrichts (vgl. u.a. Niedersächsisches Kultusministerium 2017), standen bislang im (inter-)nationalen Raum Studien, die die Zeitzeug*innenbefragung als didaktisches Arrangement historischen Lernens im Sachunterricht untersuchen sowie die Kinderperspektive auf die Methode der Zeitzeug*innenbefragung erfassen, aus. Entsprechend fokussiert die vorliegende, explorative und qualitativ angelegte Studie die Präkonzepte von Grundschulkindern zur Methode der Zeitzeug*innenbefragung. Mittels leitfadengestützter teilstandardisierter Einzelinterviews wurden die Präkonzepte zur Methode sowie zum Wissenschaftsverständnis bezüglich Zeitzeug*innen als historische Quelle rekonstruiert (vgl. Fuhs 2012, Helfferich 2011). Das Sample setzte sich aus Grundschulkindern der zweiten und vierten Klasse zusammen. Zur Bearbeitung und Auswertung des Datenmaterials diente eine in Anlehnung an die Lehr- und Lernforschung adaptierte Vorgehensweise der Qualitativen Inhaltsanalyse, die entsprechend modifiziert und erweitert wurde (vgl. Kuckartz 2018). Die Befunde der Studie zeigen differenzierte Präkonzepte der interviewten Zweit- und Viertklässler*innen zum Kontext der Methode der Zeitzeug*innenbefragung auf. Im Weiteren verweisen die Befunde darauf, dass die Zeitzeug*innenbefragung als Unterrichtsmethode ihre Legitimation im historischen Lernen mit Beginn des Anfangsunterrichts in der Grundschule hat.
Keywords: Präkonzepte; Zeitzeugenbefragung; Historisches Lernen; Sachunterricht; qualitative Forschung